A Study on the Chemical Reactions Involved in the Process of the Formation of Dye with the Help of Chrysodine and 8-Hydroxy Quinoline Ligands: The Relationship Between Chelation and Antimicrobial Activity of Oxine (Journal of Advances and Scholarly Researches in Allied Education, 2015)
8-Hydroxyquinoline (8-quinolinol, oxine) might be thought to function as a phenol, but of the 7 isomeric Hydroxyquinolines only oxine exhibits significant antimicrobial activity, and is the only one to have the capacity to chelate metals. If the hydroxyl group is blocked so that the compound is unable to chelate, as in the methyl ether, the antimicrobial activity is destroyed. The relationship between chelation and activity of oxine has been investigated. Oxine itself is inactive, and exerts activity by virtue of the metal chelates produced in its reaction with metal ions in the medium. Used by itself or as the sulphate (Chinosol) or benzoate in antiseptics, the effect is bacteriostatic and fungistatic rather than microbiocidal. Inhibitory action is more pronounced upon gram-positive than gram-negative bacteria the growth-preventing concentrations for staphylococci being 10 ppm for streptococci 20 ppm for Salmonella typhosa and for E. coli 100 ppm.